Weight Suppression in Bulimia Nervosa: Relationship with Cognitive Behavioral Therapy Outcome - Dawkins, Hayley; Watson, Hunna; Egan, Sarah; Kane, Robert (John Wiley & Sons, Inc., 2013)
Objective: In light of prior inconsistent findings, this study revisits the relationship between weight suppression and treatment outcome in bulimia nervosa. Aside from differences in methodology, we propose that moderator effects may assist the field in interpreting previous inconsistency. In this study, we considered moderators that might place individuals at risk of broad cognitive and biobehavioral mechanisms implicated in weight (dys)regulation and binge eating, and that within the context of a history of weight suppression, might be associated with especially poor outcomes. Method: Participants were 117 female outpatients aged 16–54 years (M = 25.5) with bulimic disorders treated with enhanced cognitive behavioral therapy. Results: Logistic regression indicated that higher pretreatment weight suppression did not predict drop-out or poor treatment outcome (nonabstinence from binging and purging). Moderators of parental history of overweight, childhood body shape, pretreatment body mass index, and the difference between highest and lowest ever adult body weight were analyzed, but no moderator effects were apparent. Discussion: This study, along with other negative studies, calls into question the association between weight suppression and treatment outcome. We maintain that moderators may account for inconsistencies, but no candidates were identified in this study. Moderator models could assist us to refine conceptualizations of why some patients high in weight suppression may be vulnerable to poor treatment adherence and outcome and to establish clinical interventions that enhance prognosis.